EDUCATION AND RESEARCH IN THE ERA OF DIGITAL TRANSFORMATION (Ustozlar uchun, 2025)
This article provides a brief overview of education and research in the era of digital transformation, encompassing what digital transformation entails, the integration of technology into education and science, along with concepts such as online platforms and artificial intelligence-based learning. Furthermore, it provides a brief explanation of how modern technologies should be utilized in each form of education. Additionally, the digitalization processes in Uzbekistan, existing challenges, and ways to address them are analyzed.